Pengaruh Intensitas Penggunaan Gawai Terhadap Prestasi Belajar Siswa Kelas VII pada Mata Pelajaran IPS di SMP Al-Falah Bekasi - Winda Desya Ramadhani; Supriyadi; Irvia Eriza (Indo Publishing, 2025)
This study aims to determine the effect of device usage intensity on the learning achievement of seventh-grade social studies students at SMP Al-Falah Bekasi. The research method used was an associative quantitative approach. The sampling technique used Isaac Michael random sampling with a 5% error threshold, involving 142 respondents. The results showed a t-value of -3.239 with a p-value of 0.001 < 0.05. Therefore, H0 was rejected, indicating that device usage intensity has a significant negative effect on student achievement. The resulting linear regression equation is Y = 86.315 + -0.050X. This means that every 1-unit increase in device usage intensity will decrease learning achievement by 0.050 points. The coefficient of determination (R²) test was 0.070, indicating that device usage intensity explains 7% of learning achievement, while the remaining 93% is explained by other factors not explained in this study.